Roles for Ca2+ Mobilization and Its Regulation in Mast Cell Functions - Holowka, David; Calloway, Nathaniel; Cohen, Roy; Gadi, Deepti; Lee, Jinmin; Smith, Norah L.; Baird, Barbara (Frontiers in Immunology, 2012)
Mobilization of Ca2+ in response to IgE receptor-mediated signaling is a key process in many aspects of mast cell function. Here we summarize our current understanding of the molecular bases for this process and the roles that it plays in physiologically relevant mast cell biology. Activation of IgE receptor signaling by antigen that crosslinks these complexes initiates Ca2+ mobilization as a fast wave that is frequently followed by a series of Ca2+ oscillations which are dependent on Ca2+ influx-mediated by coupling of the endoplasmic reticulum luminal Ca2+ sensor STIM1 to the calcium release activated calcium channel protein Orai1. Granule exocytosis depends on this process, together with the activation of protein kinase C isoforms, and specific roles for these signaling steps are beginning to be understood. Ca2+ mobilization also plays important roles in stimulated exocytosis of recycling endosomes and newly synthesized cytokines, as well as in antigen-mediated chemotaxis of rat mucosal mast cells. Phosphoinositide metabolism plays key roles in all of these processes, and we highlight these roles in several cases.